"The Effect of Plyometric Strength Training on Biomechanical Variables of Youth Volleyball Players' Wall Blocking Skill" (Eurasian Journal of History, Geography and Economics, 2023)
The skill of wall blocking is one of the motor skills encompassed by evolution. High achievements in this skill depend on specific technical stages that must be addressed and developed to the highest possible physical level, upon which other biomechanical variables can be built. Hence, the importance of rebound strength followed by important physical abilities for the blocker, as they maintain positive kinetic momentum between the moments of support and push-off. The researcher noticed that rebound strength training did not receive the necessary practical attention within the training curricula for wall blocking skills, and there was a lack of clarity in the ability to achieve and develop the physical capabilities associated with all mechanical conditions. The study aimed to identify the impact of rebound strength training on developing some biomechanical variables related to volleyball wall blocking skills for the research group. The researcher assumed in this study the presence of statistically significant differences between the pre-test and post-test measurements in the values of some biomechanical variables related to volleyball wall blocking skills in the research sample. As for the research methodology, the researcher used an experimental approach with a single experimental group to suit the nature of the research. The research sample was selected by the deliberate method, consisting of (10) players from the Shatrah Volleyball Club in the youth category. The most important conclusions were that all the exercises used to develop muscle strength, biomechanical, and anatomical foundations, whether for leg muscles, trunk, or arms, increased the efficiency of internal strength, thus positively affecting the biomechanical variables of the wall blocking skill. The researcher recommended emphasizing the implementation of rebound strength training periodically and using various assistive devices and tools, especially for the muscles of the lower limbs, core, and arms due to their importance in achieving integration between the physical and biomechanical aspects of volleyball wall blocking